Global Geospatial Information Management: un'iniziativa delle Nazioni Unite (GEOmedia, 2010)
What is Global Geospatial Information ManagementThere is general agreement of an urgent need for an inter-government consultative mechanism that can play a leadershiprole in setting the agenda for the development of global geospatial information and to promote its use to address key global challenges; to liaise and coordinate among Member States, and between Member States and international organizations.